Perbandingan Efek Refrigerasi dan Waktu Pendinginan pada Refrigerator yang Menggunakan Variasi Pemasangan Heat Exchangers - Ega Taqwali Berman (Teknik Mesin "TEKNOLOGI", 2012)
This studyaimstocompare the refrigeratingeffect and chilling period to the refrigerator with variationsheat exchangerinstallation.Tests performed on the test section consists of two types of heat exchangers, Suction-Liquid Heat Exchanger (SLHX) and Tube in Tube Heat Exchanger (TiTHX). Test data measured at the temperature of the cooling load temperature of 60C to - 60C and the working fluid is used as a cooling medium is a refrigerant 12. As a result, it was obtained that in this research wasrefrigerating effectby system that uses TiTHX  0.6% greater than the refrigeration system that uses SLHX. This is due to there is little difference between the temperature of evaporation and temperature liquid refrigerant that will go into the expansion device on a system that uses TiTHX than refrigeration systems that use SLHX. Chilling period required to reach the steady state temperature measurements (60C) and final conditions (-60C) is shorter on a system that uses TiTHX than systems that use SLHX. Keywords : refrigerator, heat exchangers, refrigerating effect, chilling period.